Tertiary education in Colombia : paving the way for reform - World Bank. (Washington, D.C. : World Bank, 2003)
The book is part of the World Bank Country Studies series published with the approval of the subject government to communicate the results of the Bank's work on the economic and related conditions of member countries to government and to the development community.
Includes bibliographical references (p. 197-205)
opc 09/01/17
Loans
Keywords: Education, Higher; Professional education; Educational change